Ophiopogon malipoensis (Asparagaceae), a new species from Yunnan, Southern China - Hao, Jia-Chen; Feng, Hui-Zhe; Tan, Kun; Lin, Qin-Wen (Phytotaxa, 2025)
Ophiopogon malipoensis, a distinct new species from Yunnan Province, China, is described and illustrated. The new species is similar to O. peliosanthoides in its habit, broad leaf blades with a distinct petiole and pinnate-parallel venation, and the racemose inflorescence of externally purplish flowers. It differs, however, by the stout ginger-like rhizome, larger (30–39 × 4.4–5 cm) apically acuminate lanceolate leaf blades that are light green on the abaxial surface and with more lateral veins (12–15 pairs), connate anthers, and inconspicuous filaments.